Reducing the Impact of Plastic Waste in Kijang Makmur Village Through Ecobrick and Ecoprint Education: Mengurangi Dampak Limbah Plastik Desa Kijang Makmur Melalui Edukasi Ecobrick Dan Ecoprint - Riska Dwi Indriani; Fessy Nabilah Ananda; Samuel Amin Sinambela; Amanda Puspita Rahmawati; Nurul Haqqi Ramadhani (Institute of Educational, Research, and Community Service, 2023)
Ecobricks are a creative effort to manage plastic waste into useful objects, reducing pollution and toxins caused by plastic waste. The ecoprint technique was used to decorate the surface of a fabric with various shapes and colors (staining) produced from natural materialsThe aimed of this work program activity was to reduced the impact of plastic waste in Kijang Makmur Village through ecobrick and ecoprint education. Ecobricks specifically aim to manage inorganic waste that was difficult to decompose into useful products or goods and ecoprint specifically aims to reduce the used of plastics which can later become waste by used ecoprinted tote bags that can be used for a long period of time. The method used in this work program activity was the method of direct explanation and coercion. The result of making ecobricks was the production of a small table where plastic bottles of the same size were arranged, combined and wrapped around a clear cover which was used to attach one bottle to another. The result of making ecoprints was the production of totebags with natural decorations derived from leaf or flower extracts which can later be used to anticipate the use of plastic